Diffusion-weighted MRI: In differential diagnosis of liver masses - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2017)
Objectives: The purpose of our study was to determine apparent diffusion coefficients (ADCs) of focal liver lesions on the basis of respiratory triggered diffusion-weighted single-shot echo-planar MR imaging (DWI-SS-EPI) sequence and to evaluate whether ADC measurements can be used to characterize lesions. Patients and Methods: One hundred and eighteen patients with 134 focal liver lesions [35 cysts, 48 hemangiomas, 4 focal noduler hyperplasias (FNH), 31 metastases, 14 hepatocellular carsinomas (HCCs), 1 fibrolamellar carsinoma, 1 cholangiocellular carcinoma; mean size 18.4 mm; range 10-140 mm] were examined on a 1.5-T system using respiratory triggered DWI-SS-EPI (b-values: 50, 400, 800 s/mm(2)). Results: Results were correlated with characteristic MRI findings, histopathologic data and follow-up imagings. The ADCs of different lesion types were compared and lesion differentiation using optimal thresholds for ADCs was evaluated. Mean ADCs (x10(-3) mm(2/)s) were 2.15, 1.57, 1.16, 1.08, 1.03 for cysts, hemangiomas, FNHs, metastases and HCCs, respectively. Mean ADCs differed significantly for all lesion types except metastases, HCCs and FNHs. Overall, 88.5% of lesions were correctly classified as benign or malignant using a treshold value of 1.20x10(-3)mm(2)/s. Conclusion: Measurements of the ADCs of focal liver lesions on the basis of a respiratory triggered DWI-SS-EPI sequence may constitute a useful supplementary method for lesion characterization.
Keywords: Respiratory triggered diffusion-weighted single-shot echo-planar magnetic resonance imaging technique; Apparent diffusion coefficients; Focal liver lesions